Stem-Loop RT-qPCR as an Efficient Tool for the Detection and Quantification of Small RNAs in Giardia lamblia - Marcial-Quino, Jaime; Gómez-Manzo, Saúl; Fierro, Francisco; Vanoye-Carlo, America; Rufino-González, Yadira; Sierra-Palacios, Edgar; Castillo-Villanueva, Adriana; Castillo-Rodríguez, Rosa; Rodríguez-Bustamante, Eduardo; Arreguin-Espinosa, Roberto; Reyes-Vivas, Horacio (Genes, 2016)
Stem-loop quantitative reverse transcription PCR (RT-qPCR) is a molecular technique used for identification and quantification of individual small RNAs in cells. In this work, we used a Universal ProbeLibrary (UPL)-based design to detect—in a rapid, sensitive, specific, and reproducible way—the small nucleolar RNA (snoRNA) GlsR17 and its derived miRNA (miR2) of Giardia lamblia using a stem-loop RT-qPCR approach. Both small RNAs could be isolated from both total RNA and small RNA samples. Identification of the two small RNAs was carried out by sequencing the PCR-amplified small RNA products upon ligation into the pJET1.2/blunt vector. GlsR17 is constitutively expressed during the 72 h cultures of trophozoites, while the mature miR2 is present in 2-fold higher abundance during the first 48 h than at 72 h. Because it has been suggested that miRNAs in G. lamblia have an important role in the regulation of gene expression, the use of the stem-loop RT-qPCR method could be valuable for the study of miRNAs of G. lamblia. This methodology will be a powerful tool for studying gene regulation in G. lamblia, and will help to better understand the features and functions of these regulatory molecules and how they work within the RNA interference (RNAi) pathway in G. lamblia.